Grandisin induces apoptosis in leukemic K562 cells - Alane Pereira Cortez; Elizabeth Gomes Paulino Menezes; Polyana Lopes Benfica; Alexandre Pereira dos Santos; Larissa Moreira Cleres; Higor de Oliveira Ribeiro; Eliana Martins Lima; Massuo Jorge Kato; Marize Campos Valadares (Universidade de São Paulo, 2017)
Abstract In this study, the potential antileukemic activity of grandisin, a lignan extracted from Piper solmsianum, was evaluated against the leukemic line K562. The cytotoxicity of grandisin (0.018 to 2.365 µM) was evaluated in K562 and normal peripheral blood lymphocytes by Trypan Blue Exclusion and MTT methods after 48h exposure to the drug. In both methods, cellular viability was concentration-dependent and the IC50 values were lower than 0.85µM. Analysis of K562 cells after treatment with grandisin showed that the cell cycle was arrested in the G1 phase with a 12.31% increase, while both S and G2 phases decreased. Morphological studies conducted after the exposure of K562 to grandisin revealed changes consistent with the apoptosis process, which was confirmed by anexin V stain and caspase activation. Thus, lignan grandisin showed antileukemic activities against the K562 cell line and the cell death process occurred via apoptosis.